COMPARATIVE ANALYSIS OF BANKRUPTCY PREDICTION METHODS OF ALTMAN, SPRINGATE, AND ZMIJEWSKI - Ahmad Faizin; Muhammad Ulin Nuha (International Journal of Management, Business, and Social Sciences, 2023)
This study aims to determine the results of the bankruptcy prediction calculation score, to find out whether there are differences in bankruptcy prediction and to find out which bankruptcy prediction model is the most accurate in predicting bankruptcy altman, springate and zmijewski methods. This type of research uses quantitative research with a comparative approach. This study uses the population of real estate and property companies listed on the IDX in 2019-2021 on the www.idx.com website. Sampling was carried out by purposive sampling so that a sample of 80 companies was obtained. Data analysis techniques in this study used the Normality Test and the Kruskall Wallis Test using SPSS 26 and the Accuracy Level Test. The results of the Kruskal Wallis Test illustrate that there is a significant difference between the three methods used with significant values of 0.005 or < 0.05. The results of this study revealed that the Zmijewski Model is the most accurate bankruptcy prediction model in predicting the bankruptcy of real estate and property companies with a total accuracy rate of 86.67% and an error rate of 13.33%.